Morphological characterization of 25 varieties of starchy maize evaluated in two localities of the province of Tayacaja, Huancavelica - Prieto Rosales, Gino Paul (2022)
Starchy corn is considered one of the main foods of the inhabitants of the Peruvian highlands, where most of the production is destined for self-consumption, in different forms. The main objective of this study was to determine the morphological characterization of 25 varieties of starchy maize, evaluated in 2 environments in the province of Tayacaja, Huancavelica, Peru, in the 2019-2020 crop cycle. For the morphological characterization, 24 plant and ear characters were used, analyzed using univariate and multivariate analysis of variance. In the multivariate analysis, principal components (PC) and cluster analysis with Ward's method were used. The agronomical studies allowed to demonstrate the superiority of the improved varieties for most of the characters studied, which shows the importance of plant breeding to obtain genotypes with outstanding agronomic performance. According to the PC analysis, the first three PCs explained 67 % of the phenotypic variation observed in the group of populations studied. The morphological characterization classified the varieties into six well-defined groups, based on the traits analyzed. All traits used in the study were appropriate for the classification and characterization of the phenotypic variability of local maize varieties, except for grain yield, grain index and the number of secondary branches in the spike, for which no differences were observed between the variety’s groups.